2012
DOI: 10.4103/2229-5178.101811
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial aspects of Hansen′s disease (leprosy)

Abstract: In general, the prevalence of psychiatric disorders among people with Hansen's disease has greatly increased to date. However, inadequate psychiatric care of people with Hansen's disease is an area of increasing concern. Many studies have been conducted in India and abroad to find out the prevalence of comorbid psychiatric disorders in patients suffering from Hansen's disease. Although efforts have been made by the government and international organizations to solve the medical problems among this group of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 15 publications
3
46
0
9
Order By: Relevance
“…Among chronic illnesses, studies show that from 20% to 30% of patients with hematological diseases 20 and diabetes mellitus 21,22 show significant depressive symptoms. Depression is very common with leprosy, 5,11,12 corroborating the results of this study in which the presence of moderate to serious symptoms of depression was relevant and can signal the possibility of having clinical depression.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Among chronic illnesses, studies show that from 20% to 30% of patients with hematological diseases 20 and diabetes mellitus 21,22 show significant depressive symptoms. Depression is very common with leprosy, 5,11,12 corroborating the results of this study in which the presence of moderate to serious symptoms of depression was relevant and can signal the possibility of having clinical depression.…”
Section: Discussionsupporting
confidence: 85%
“…5,6 It is treated as a chronic infecto-contagious disease that develops slowly, caused by the Myobacterium Leprae bacteria, which damages peripheral nerves causing sensory, motor, and autonomic alterations in the face (eyes and nose), hands, and feet. This disease affects people of all ages, especially those in the economically active age bracket.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leprosy patients may face the effects of stigma and different forms of discrimination, such as rejection, abuse, divorce, or loss of employment, leading to reduced self-esteem and loss of respect from their communities [4–6]. Interpersonal relationships, social status, mobility, and dignity suffer [5, 6] and may cause anxiety, depression, emotional stress, isolation, and suicide or attempted suicide. Multiple studies found women to be more affected by leprosy and its stigma than men [3, 4, 6–9].…”
Section: Introductionmentioning
confidence: 99%
“…O estigma não é um fenômeno único, possui vários componentes: o autoestigma (vergonha, baixa autoestima pelo portador da doença), o estigma público (por exemplo, o preconceito do público em geral), que também está associado à restrição da participação social e da discriminação da pessoa infectada 7 . No nível individual, como consequência do preconceito, os portadores da hanseníase também estão mais sujeitos à desagregação familiar, divórcio e desemprego 13 . O estigma, visto como um processo social, envolve não somente os indivíduos afetados, mas desempenha um papel em todos os aspectos do discurso da hanseníase, desde a organização dos cuidados de saúde e da identidade social dos trabalhadores, até a formulação de futuras intervenções 14 .…”
Section: Introductionunclassified